Influence of saline exposure and freeze-thaw effects on class C fly ash geopolymer mortars using the Taguchi method - Hasan Altawil (Results in Engineering)
This study investigates the durability performance of ambient-cured geopolymer mortars composed of Class C fly ash and silica fume when exposed to two aggressive conditions: freeze–thaw cycles and saline immersion. The Taguchi L₁₆ orthogonal array was employed to examine the effects of four key parameters: sodium hydroxide (NaOH) molarity (10, 12, 14, and 16 M), alkaline activator-to-binder (AA/B) ratio (0.3, 0.35, 0.4, and 0.45), sodium silicate-to-sodium hydroxide (SS/SH) ratio (1.75, 2.0, 2.25, and 2.5), and water-to-geopolymer solids (W/GS) ratio (0.35, 0.45, 0.55, and 0.65). Durability was assessed based on compressive strength retention and mass loss. The results showed that the optimal mix under freeze–thaw cycles (10 M NaOH, W/GS = 0.35, SS/SH = 2.0, AA/B = 0.4) retained 96.39% of its initial strength, while the most resistant mix under saline conditions (10 M NaOH, W/GS = 0.35, SS/SH = 1.75, AA/B = 0.4) exhibited a 78.12% strength gain after NaCl exposure. ANOVA analysis confirmed that W/GS was the most influential factor under freeze–thaw conditions (52.11% contribution), while SS/SH was dominant under saline conditions (39.91%). The incorporation of silica fume improved pore refinement and overall durability in both scenarios. Although SEM/XRD analyses were not conducted, the study provides robust parametric insights into durability optimization using the Taguchi method. These findings support the use of ambient-cured geopolymer mortars as sustainable alternatives in cold and coastal environments.